Institutional Framework for Japanese Private Investors to Ensure Safe Investments in Developing Countries - Williams, Patrick E. (Journal of Global Economy, Business and Finance, 2025)
Іnvеstmеnt projесts arе еssеntіally subjесtеd to varіous forms of risk that can impact expected performance such as the external environment, specific endogenous factors, operational structure, and functional investment objectives. This study explores the risks foreign investors, especially Japanese investors, will face in developing or underdeveloped countries, especially in trade secrets, trademarks, copyrights, patents, licensing, tax holidays, trade unions, and policies. Investors use personal relationships with business partners and government connections to reduce uncertainty by weak legal rules rather than substitutes for formal legal rules such as bilateral investment agreements and special economic zones. This research takes both primary and secondary sources of information. The main sources are local and foreign statutes, common law, codes of ethics, international documents, judicial decisions, and treaties. This essay recommends improving global trade and investment rules to prevent protectionist trade and investment.